To What Extent Might Identity Theories Help Understand the Learning Process of EFL Learners - Susiati, Susiati; Exaputri, Avelia Yonanda (Prosiding University Research Colloquium, 2019)
This study investigates how identity theories help understand the learning process of EFL learners of Department of English Education, Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta. Adopting three different views on identity: psychological, social and negotiated views, this study explored the learners‘ identity based on two backgrounds: Islam and Javanese ethnic in English debating activities in a speaking class. Other than the learners’ unwillingness to communicate, the results show there is a similar view of learners from Islamic and Javanese backgrounds that feminism issues are sensitive case to be debated in the activities. The gap lies on their personal view that from the perspective of Islam, it is seen as a ‘sinful’ motion. Whereas, from that of Javanese ethnic, feminism issues are seen taboo regarding the Javanese value about women as konco wingking (domestic workers). This leads the lecturers to reconsider the motions to be launched in the debating activities to build a conducive class.